Empowering youth for sustainable tourism: the mediating roles of social innovation in promoting local community development / Noorlailahusna Mohd Yusof ... [et al.] - Mohd Yusof, Noorlailahusna; Azizan, Intan Syahriza; Ahmad, Nor Ardyanti; Ismail, Junaida; Yusoff, Siti Norfazlina (Universiti Teknologi MARA, Sabah, 2025)
This study explores the relationship between youth empowerment, social innovation, and community development in the context of sustainable tourism. As youth play a critical role in shaping the future of tourism, understanding how their empowerment influences local development is essential for fostering sustainable practices. The aim of the study is to examine how social innovation mediates the relationship between youth empowerment and community development, with a particular focus on the role of young people in promoting sustainable tourism. Using a narrative review methodology, the research synthesizes existing literature from the Scopus database to identify key themes and theoretical perspectives surrounding youth involvement in tourism, community development, and social innovation. The findings reveal that empowering youth leads to increased community participation and the development of innovative solutions that address local challenges. Social innovation plays a crucial role in mediating the effects of youth empowerment on community development by facilitating inclusive governance, capacity building, and the preservation of cultural and natural resources. The study contributes to both theoretical and practical discussions on youth involvement in sustainable tourism, highlighting the significance of inclusive governance and stakeholder collaboration. However, the study's limitations include its focus on specific geographic contexts, suggesting that further research is needed to explore cross-cultural dynamics and the long-term impacts of youth-led initiatives on community development.